Neoplastic transformation of an implant goitre thyroid level from a thyroidectomy scar - Delgado, Bolívar; Estapé, Gonzalo; Toledo, Nancy; Iraola, María L (Cirugía del Uruguay, 1990)
The authors presents the case of a patient who was surgically treated for a multinodular goiter and 18 years later turns up wjth a remanent thyroid carcinoma and a cancerous nodule of the same nature at the thyroidectomy scar. The possible pathological exp/anations for such an exceptional situation are discussed.